Role of artificial intelligence in moderating the innovative financial process of the banking sector: a research based on structural equation modeling - Rabbani, M. R.; Lutfi, A.; Ashraf, M. A.; Nawaz, N.; Ahmad Watto, W. (Frontiers in Environmental Science, 2023)
The technological advancement of the banking sector in the modern era is based on the type of services provided as per the requirements and facilitation of customers backed by an innovative process of financial services along with the right use of artificial intelligence. The usage of AI in the bank’s financial system has accelerated the financial data in the banking industry providing a broader customer base in the form of digital apps, digital payments, and chat-bot systems. Pakistan is one of those countries where the system of AI for the banking industry is still under process as compared to developed nations. This research seeks to find the moderating role of AI in the association between a bank’s innovative financial process and the bank’s market share. The data was analyzed using SPSS and Smart PLS software. The estimations were done using structural equation modeling estimation techniques like measurement model, outer loading, convergent validity, discriminant validity, and SEM estimations. The initial estimations indicated factor as well as construct reliability and validity. The study concluded that an innovative financial process plays an important role in enhancing the bank’s market share. However, artificial intelligence could not significantly moderate the relationship. The policymakers in the banking industry of Pakistan need to consider the up-gradation in the system of their financial process by innovation and artificial intelligence usage awareness in their existing staff as well their banking customers. This study adds the existing literature with the usage of artificial intelligence in the banking sectors and their process of financial transactions. The outcomes of this study are comparable within the banking sector only. Future research may include a similar model for Islamic as well as commercial banks in a comparative model. Additionally, future research may also include more banks as innovative financial institutions to get a greater sample size for a possible influence of artificial intelligence.